Florence Heritage data System. Un modello di controllo e valutazione per i siti Patrimonio Mondiale - Capitanio, Carolina; Chiesi, Daniela; Franco, Martina (Restauro Archeologico, 2023)
Florence Heritage Data System is part of the projects for the protection and enhancement of the Historic Urban Landscape (HUL), contributing to the knowledge, use, protection and management of the Historic Centre of Florence. The main target is creationing a World Heritage sites control and evaluation model, using the system of data and techniques to evaluate architectural and urban restoration projects, in the context of dynamic transformations, on the historicized fabric. A necessary tool for the Florence World Heritage and Relations with UNESCO Office; it is usefull to the Periodic Reports, to the evaluations of the territorialized discipline and of the specific regulation on World Heritage (HIA), for the integration and identification of «elements of heritage» within «transformation projects», architectural diagnostics and cultural heritage cataloging and cartographic activities.